The effect of the γ′ morphology on stress-rupture properties of IC21 alloy at 850°C. (May 2015) - Zhang, H.; Liang, Y. F.; Li, S. S.; Zhou, J.; Gong, S. K.
Abstract : In this study, the effect of the γ′ morphology on stress-rupture properties of single crystal alloy IC21 at 850°C 500 MPa − 1 was investigated. Special heat treatment (HT) with different cooling procedure and holding temperature were conducted to samples before the stress-rupture test. The longest stress-rupture life and the smallest elongation were obtained after HT3 treatment. Microstructure examination shows that micro-raft was built during intermediate temperature stress-rupture test after HT3 treatment. Moreover, transmission electron microscopy (TEM) analysis of the stress-ruptured samples reviews that with the change of the γ′ morphology, the dominant deformation mechanism has been changed from the shearing of the < 112> super-partial dislocations to the Orowan by-passing mechanism.